Integrated Education in Poland - Between the Explicit "Legal"/Legitimate and "Apparent" Dimension - Karolina Kołodziejczak; Katarzyna Smoter (Vasyl Stefanyk Precarpathian National University, 2019)
An integrated school, like any educational institution, creates a specific field which is a combination of experiences of the people entering its area, the relations between them, attitudes and behaviours that affect both its "open" and "hidden" dimension. In this article the two dimensions are mentioned as: "integrated schools in Poland - formal assumption" and "integrated education in the hidden dimension of the school culture". These different reviews of the problem generate different consequences for understanding these two dimensions. Effective integration of people with disabilities into society should be based on ensuring continuity of activities improving from the moment of disability, to becoming independent, and also to organize a system of broad support for the development of a child with disabilities. It is also important to reflect on the discrepancies that arise between how integration makes itself present in formal records and how to make the postulates look more realistic. Its highest level of social integration is accompanied to a great extent by "being with each other" and not "being beside", the possibility of not only protecting and supporting the weaker, but also mutual exchange between disabled and nondisabled people.